Offshore aeolian sediment transport across a human‐modified foredune. Issue 1 (14th September 2017) - Nordstrom, Karl F.; Jackson, Nancy L.
Abstract: Concepts derived from previous studies of offshore winds on natural dunes are evaluated on a dune maintained for shore protection during three offshore wind events. The potential for offshore winds to form a lee‐side eddy on the backshore or transfer sediment from the dune and berm crest to the water are evaluated, as are differences in wind speed and sediment transport on the dune crest, berm crest and a pedestrian access gap. The dune is 18–20 m wide near the base and has a crest 4.5 m above backshore elevation. Two sand‐trapping fences facilitate accretion. Data were obtained from wind vanes on the crest and lee of the dune and anemometers and sand traps placed across the dune, on the beach berm crest and in the access gap. Mean wind direction above the dune crest varied from 11 to 3 deg from shore normal. No persistent recirculation eddy occurred on the 12 deg seaward slope. Wind speed on the berm crest was 85–89% of speed at the dune crest, but rates of sediment transport were 2.27 times greater during the strongest winds, indicating that a wide beach overcomes the transport limitation of a dune barrier. Limited transport on the seaward dune ramp indicates that losses to the water are mostly from the backshore, not the dune. The seaward slope gains sand from the landward slope and dune crest. Sand fences causing accretion on the dune ramp during onshore winds lower the seaward slope and reduce the likelihood of detached flows during offshore winds. Transport rates are higher in access gaps than on the dune crest despite lower wind speeds because of flatter slopes and absence of vegetation. Transport rates across dunes and through gaps can be reduced using vegetation and raised walkover structures. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Sediment transport by shore‐normal offshore winds was evaluated on a dune maintained for shore protection. The seaward slope gained sand from the landward slope and dune crest while losses to the water were mostly from the backshore. Sand fences causing accretion on the dune ramp lower the seaward slope and reduce the likelihood of detached flows during offshore winds.